Analysis of work posture at grey's warehouse in PT Surya Putra Mulia - Ambang Rizki Aji Nugrahanto; Maria Puspita Sari (Politeknik Meta Industri, 2021)
PT Surya Putra Mulia is a company that produces gray (greige) using the knitting process. This research is focused on the warehouse section on the loading process finished goods. In the warehouse section there are some excessive physical activities due to activities are carried out manually. Measurement of work posture is needed to determine whether the work posture carried out by the operator is good and ergonomic. Assessment of work posture is carried out using the Rapid Entire Body Assessment (REBA) method. Based on an assessment using the REBA (Rapid Entire Body Assessment) method, it shows that the withdrawal of finished goods includes a moderate level of risk, which means that improvements are needed. The activity of loading finished goods onto trucks (figure 3) includes a moderate risk level which means that repairs are needed, while in Figure 4 it is a high risk level which means that immediate corrective action is needed. For the preparation of finished goods on trucks, it is a moderate risk level, which means that repairs are needed. So that in the process of withdrawing finished goods, proposals are given to reduce the burden being transported. Then add a tool in the process of loading finished goods to the truck in the form of a hand stacker.